Wearable and Portable Devices in Sport Biomechanics and Training Science (MDPI - Multidisciplinary Digital Publishing Institute, 2024)
Sport biomechanics and training have been traditionally tested under laboratory conditions, requiring both specific conditions and expensive equipment. The novel use of wearable devices aims to fulfill the lack of ecology for such measures and provides an affordable and easy-to-use option to perform biomechanics. Lately, wearable sensors have allowed for the quantification of performance and workload by providing mechanical and physiological parameters and their popularity has grown exponentially. In this context, more and more wearable sensors are commercially available and, when applied to biomechanics, these devices are able to provide both kinetic and kinematic variables, consequently improving the feasibility and testing time of such assessments and, therefore, becoming a real alternative for sport practitioners and researchers. Additionally, wearable devices allow real-time monitoring and biofeedback.